1981
DOI: 10.1021/ac00225a048
|View full text |Cite
|
Sign up to set email alerts
|

Determination of complexing capacity of fulvic acid for copper(II) and cadmium(II) by dialysis titration

Abstract: The complexing capacity of a solution is a measure of the metal Ion blndlng ability of the dissolved ligands. The purpose of this study Is to evaluate dlalysls titration as a method of determlnlng the complexlng capacity of soil-derlved fulvic acld (SFA). In a prellmlnary experiment, we titrated 6.25 pM ethylenediaminetetraacetlc acld (EDTA) at pH 6 with Cu2+ and Cd2+ and obtained complexing capacity values within 2.4% of theoretlcal. Next, 15.5 pM SFA was titrated with Cu2+ or Cd2+ at pH 5, 6, and 7 during 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…Moreover, several attempts have been made to determine the complexing capacity of humic substances (Truitt and Weber 1981;Yamada et al 1987). Based on this concept, we attempted to evaluate the maximum Cu-binding capacity (MCBC) of the root cell wall fraction, according to the method described by Nishimura (1979).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several attempts have been made to determine the complexing capacity of humic substances (Truitt and Weber 1981;Yamada et al 1987). Based on this concept, we attempted to evaluate the maximum Cu-binding capacity (MCBC) of the root cell wall fraction, according to the method described by Nishimura (1979).…”
Section: Resultsmentioning
confidence: 99%
“…A non-electrostatic model was chosen as only one ionic strength was explored (0.01 M), and previous studies have demonstrated that electrostatic surface field effects on protonation are minimal for bacterial surfaces (Borrok et al, 2004) and humic and fulvic acids (Truitt and Weber, 1981). Titration data were modeled using leastsquares optimization as implemented in FITEQL 4.0 (Herbelin and Westall, 1999).…”
Section: Alkalimetric Titrationsmentioning
confidence: 99%
“…As adsorption of free Cd by mucin-reactive sites occurs, Cd 2+ in solution crosses the semipermeable membrane until equilibrium is reached. To achieve Cd 2+ equilibrium between the diffusate and the retentate solutions, the experiments were placed in an incubator at 25 uC while undergoing constant agitation (40 rpm) for a period of 24 hours (Truitt and Weber, 1981).…”
Section: Cadmium Complexationmentioning
confidence: 99%
“…Solid KC1 was added to the outside solutions until the ionic strength as measured by a conductivity meter (Model 441, Corning Inc. New York) matched that o f the inside solution. The volume ratio of outside/inside solution was set at 26: 1 (Truitt and Weber, 1981). During the dialysis process, the closed containers were continuously stirred with a magnetic stirrer at 25°C for five days.…”
Section: Equilibrium Dialysis Experimentsmentioning
confidence: 99%
“…Dissociation could occur during size exclusion chromatographic separation (Amy et al, 1987;Logan and Wagenseller, 2000). (Buschmann and Sigg, 2004;Haitzer et al, 2002;Jansen et al, 2003;Truitt and Weber, 1981). Very few studies, however, have dealt with metalloid As (Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%